Online reputation management in destination and hospitality what we know, what we need to know - Rialti, Riccardo; Kvitkova, Zuzana; Makovnik, Tomas (Emerald Publishing, 2023)
Reputation is considered one of the most relevant assets in business. Tourism and hospitality are no exception - visitors rely heavily on reviews and feedback found on online platforms to inform their decisions. Online Reputation Management in Destination and Hospitality's comprehensive collection of research decodifies the best practices existing in the market, developing innovative strategies for tourism, hospitality, and destination managers to tailor marketing communication strategies to attract attention and boost their reputation. From identifying biased fake reviews to collecting data from the largest online reviewing platforms, Online Reputation Management in Destination and Hospitality analyses the importance of reputation for consumers and their decision-making. The authors provide guidance for destination and hospitality managers on best practices emerging from real-life scenarios combined with the latest theoretical work. Unique research by chapter authors contributes to an increasingly interdisciplinary field, making Online Reputation Management in Destination and Hospitality essential reading for researchers, managers, and business owners globally and across the tourism and hospitality sector.- Resumé vydavatele
Keywords: management cestovního ruchu; internetový marketing; cestovní ruch; pohostinství; podniky; tourism management; Internet marketing; tourism; catering trade; business enterprises; elektronické knihy; kolektivní monografie; electronic books; collective monographs